2017
DOI: 10.1007/978-1-4939-6820-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Magnetic Isolation and Thermogenic Differentiation of White Adipose Tissue Progenitor Cells

Abstract: Appropriate cell models are necessary for the investigation of thermogenic beige adipocyte differentiation from progenitor cells. Here, we describe a primary cell culture method that is based on defined progenitor cells from murine white adipose tissue and aims at minimizing confounding factors including cell heterogeneity and nonphysiological differentiation inducers. Adipocyte progenitor cells are enriched by immuno-magnetic separation, expanded minimally, and induced for beige adipocyte differentiation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, this system and its regulation appear to underlie an unanticipated complexity. In fact, previous studies demonstrated the ω6 eicosanoid prostacyclin (PGI2, which is derived from ARA via COX-dependent metabolization) as a positive modulator of UCP1 expression and brite adipogenesis in human and murine cellular model systems (42,(45)(46)(47). In line with these findings, transgenic mice with constitutive overexpression of COX-2 (the inducible isoform of COX) show enhanced browning of WAT and resistance to diet-induced obesity (46).…”
Section: Discussionmentioning
confidence: 78%
“…However, this system and its regulation appear to underlie an unanticipated complexity. In fact, previous studies demonstrated the ω6 eicosanoid prostacyclin (PGI2, which is derived from ARA via COX-dependent metabolization) as a positive modulator of UCP1 expression and brite adipogenesis in human and murine cellular model systems (42,(45)(46)(47). In line with these findings, transgenic mice with constitutive overexpression of COX-2 (the inducible isoform of COX) show enhanced browning of WAT and resistance to diet-induced obesity (46).…”
Section: Discussionmentioning
confidence: 78%
“…To isolate progenitor cells for seeding or sorting [25], gWAT was dissected and digested as described previously [29], [30]. The Lin-Sca1+ fraction cells were counted using a hemocytometer and seeded on laminin-coated 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Adipose progenitors were isolated by magnetic-activated cell sorting (MACS) approach, as previously described (17,18). Briefly, the SVF …”
Section: Progenitor Isolation By Macsmentioning
confidence: 99%